Services Liberalization in ASEAN Foreign Direct Investment in Logistics. - Yean, Tham Siew; Das, Sanchita Basu ([S.l.] : ISEAS - Yusof Ishak Institute, 2017)
The services sector plays an important role in ASEAN economies as it accounts for about half of the regions GDP and more than 45 per cent of its total employment. ASEAN aspires to deepen integration in the services sector in order to enhance the sectors contribution to economic development and growth in each country. Despite this, services liberalization has progressed slowly compared to goods liberalization both at the multilateral and the regional levels. Different regulatory mechanisms across countries have contributed to the slow pace of liberalization.
Services Liberalization in ASEAN: Foreign Direct Investment in Logistics -- Contents -- List of Tables -- List of Figures -- Foreword -- Preface -- Acknowledgements -- Abbreviations -- About the Contributors -- 1. Introduction -- 2. Reforming Indonesia's Logistics Sector -- 3. FDI Liberalization in Malaysia's Logistics Services -- 4. Logistics Services Liberalization in the Philippines -- 5. Services Sector Liberalization in Singapore: Case of the Logistics Sector -- 6. Logistics Services Liberalization in Thailand -- 7. Services Liberalization in Vietnam: The Case of FDI in Logistics Sector -- 8. Services Liberalization: Case of Logistics in Brunei -- 9. FDI, Services Liberalization and Logistics Development in Cambodia -- 10. Services Liberalization in Lao PDR: FDI in Logistics Sector of a Land-linked Country -- 11. Facilitating FDI for the Logistics Sector in Myanmar: Agency, Incentives, and Institutions -- Index.
Includes bibliographical references and index.
Keywords: economic